Investigation of changes in rheological properties during processing of fermented cereal beverages - Iskakova, Janyl (J Food Sci Technol, 2019)
Many indigenous fermented foods and beverages consumed throughout the world are produced at home or in crafts enterprises. The production of fermented beverages on a large commercial or industrial scale requires clearly established technical and technological requirements. This study shows a novel way to investigate the optimal process parameters of the Kyrgyz traditional fermented beverage Bozo using rotational rheological parameters. Five significant process parameters were investigated like cooking of millet porridge, the mashing temperature, the mashing time under conditions of mixing and viscosity changes of the end product during storage. According to the gelatinization temperature of millet porridge, cooking parameters were recommended at T = 79 °C and t = 30 min. The optimum mashing temperature of millet porridge was determined to be 65 °C and mashing time under stirring conditions of millet porridge was found to be 10 min. The viscosity of the beverage Bozo was investigated after 7, 14 and 21 days of storage at 5, 10, 20, and 30 °C. The effective viscosity of Bozo was calculated using the Casson model, which increased from 39.67 to 51.25 Pa·s after 21 days of storage. The effect of temperature on effective viscosity of Bozo and the activation energy was calculated using an Arrhenius-type equation. The parameters obtained make it possible to provide food manufacturers useful information for boiling, mashing and storage parameters after fermentation as well as quality control of Bozo.